Sinapic Acid Protects Mortality and Toxicity Induced by N-Ethyl-N-Nitrosourea, a Full Carcinogen Agent, in Mice - Salimi, Ahmad; Pourgholi, Mahshad; Khezri, Saleh; Haddadi, Shadi; Asgari, Bahare (Drug Research, 2025)
We investigated, in vivo, the chemopreventive efficacy of sinapic acid, as a known radical scavenger and antioxidant on mortality and toxicity in a N-ethyl-N-nitrosourea (ENU)-induced chronic lymphocytic leukemia (CLL) model in mice.Mice were divided into three groups: control (normal saline), ENU (80 mg/kg, i.p., single dose on day 31), and sinapic acid+ENU (pretreated with 30 mg/kg of sinapic acid, i.p., daily for 30 days, followed by 80 mg/kg of ENU). Body weight changes and mortality were monitored over 120 days. After this period, the animals were sacrificed, and lymphocytes, the target cells in CLL, were isolated and evaluated for various cellular parameters.Sinapic acid significantly (P<0.001) increased mouse survival up to 71%, delayed time of death, and prevented weight loss following ENU exposure. Additionally, sinapic acid inhibited the formation of reactive oxygen species (ROS) (P<0.001), lysosomal and mitochondrial dysfunction (P<0.001), and lipid peroxidation (P<0.05) in the isolated lymphocytes. These findings indicate a protective effect of sinapic acid against ENU-induced lethal toxicity.This study confirms that sinapic acid may serve as a promising chemopreventive agent against carcinogenicity induced by alkylating agents, primarily through the inhibition of oxidative stress and lysosomal/mitochondrial dysfunction.
Keywords: cancer chemoprevention; N-nitrosoureas; leukemia; antioxidants; alkylating agents